2011
DOI: 10.1029/2010gc003482
|View full text |Cite
|
Sign up to set email alerts
|

Insights into mantle composition and mantle melting beneath mid‐ocean ridges from postspreading volcanism on the fossil Galapagos Rise

Abstract: [1] New major and trace element and Sr, Nd, and Pb isotope data, together with 39 Ar-40 Ar ages for lavas from the extinct Galapagos Rise spreading center in the eastern Pacific reveal the evolution in magma compositions erupted during slowdown and after the end of active spreading at a mid-ocean ridge. Lavas erupted at 9.2 Ma, immediately prior to the end of spreading are incompatible element depleted mid-ocean ridge tholeiitic basalts, whereas progressively younger (7.5 to 5.7 Ma) postspreading lavas are inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 105 publications
1
19
0
Order By: Relevance
“…Lower La/Yb ratios additionally indicate that lavas from unit 2 may have originated from a higher degree of partial melting than unit 1 lavas (Bourdon et al, ). We note, however, that the degree of partial melting and the mantle source composition may be linked, that is, differences in trace element ratios such as La/Yb may result from both, different degrees of enrichment in the mantle source and changes in degree of partial melting (Haase et al, ).…”
Section: Discussionmentioning
confidence: 93%
“…Lower La/Yb ratios additionally indicate that lavas from unit 2 may have originated from a higher degree of partial melting than unit 1 lavas (Bourdon et al, ). We note, however, that the degree of partial melting and the mantle source composition may be linked, that is, differences in trace element ratios such as La/Yb may result from both, different degrees of enrichment in the mantle source and changes in degree of partial melting (Haase et al, ).…”
Section: Discussionmentioning
confidence: 93%
“…Authors such as Saal et al [1998, 2005], Jackson and Hart [2006], Paul et al [2011] or Sobolev et al [2011] demonstrated that the isotopic variability in melt inclusions from oceanic island magmas was much larger than in the lavas themselves and they attributed the isotopic diversity to small scale sampling of the source material. In contrast, at the scale sampled by mid‐ocean ridge basalts or ocean island basalts, most authors suggest that the observed isotopic diversity results from melting of a heterogeneous source in which low degree melts preferentially sample the enriched material, while higher melting degrees dilute this enriched material with larger proportions of more “normal” mantle [ Niu et al , 2002; Donnelly et al , 2004; Castillo et al , 2010; Haase et al , 2011]. Using petrological arguments instead of isotopic constraints, Sobolev et al [2005, 2007] also suggested that low‐degree melts sampled fertile pyroxenite while the signature of the peridotitic source swamped high‐degree melts.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of various amounts of metasomatic/recycled components within the SMAR mantle sources can be traced back to the influence of the nearby Discovery plume (e.g., Douglass et al, 1999;le Roux et al, 2002b,c). Pyroxenite layers/lenses in a "marble-cake" like mantle have been suggested to be the enriched component in the SMAR mantle (le Roux et al, 2002c) as in other heterogeneous mantle sources of global oceanic basalts (Stracke, 2012;Stracke et al, 2003;Haase et al, 2011;Lambart et al, 2013;Gurenko et al, 2013;and references therein). Le Roux et al (2002c) estimated a maximum of 20-40% contribution from pyroxe- Fig.…”
Section: Implications For the N-and E-type Character Of Smar Basaltsmentioning
confidence: 98%